Upaya Guru Pendidikan Agama Islam dalam Meningkatkan Nilai-Nilai Religius Siswa/i di SD IT Nurul Ilmi Desa Pengabuan - Dian Nopita Sari; Ahmad Sopian; Muhammad Roihan Alhaddad (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2026)
Religious values play an essential role in shaping students' character and behavior through the practice of faith, worship, and moral conduct in everyday life. This study aims to analyze the efforts of Islamic Religious Education teachers in improving students' religious values at Nurul Ilmi Islamic Elementary School, Pengabuan Village, Abab District, Penukal Abab Lematang Ilir Regency (PALI), as well as to identify the supporting and inhibiting factors encountered during the process. The study employed a qualitative approach with a descriptive method. Data were collected through observations, interviews, and documentation, while data analysis followed three stages: data reduction, data presentation, and conclusion drawing. The findings reveal that teachers enhance students' religious values through several strategies, including habituation of worship practices, providing religious advice, serving as role models, utilizing school literacy media, and implementing the 5S culture (Smile, Greeting, Salutation, Politeness, and Courtesy). Supporting factors include the consistent implementation of religious programs, effective collaboration among teachers, parents, and the community, as well as adequate educational facilities. Meanwhile, the main obstacles include students' limited awareness of religious values, unfavorable social environments, insufficient cooperation between schools and families, the negative influence of technology and social media, and peer pressure. The study concludes that strengthening students' religious values requires continuous collaboration between schools, families, and communities, supported by consistent educational programs and exemplary teacher behavior to foster students' spiritual and moral development.